Plan de marketing digital para el programa ingeniería industrial (Universidad Antonio Nariño Sede Villavicencio 2019) (2020)
This investigation has a mainly objective, which is to propose a digital marketing plan as a stimulus for innovation and development of the brand positioning of the Industrial engineering program in the University Antonio Nariño of Villavicencio; certainly, it is so important for the University Antonio Nariño to have a clear strategy for the plan of digital marketing, thus, how it happened before UAN has been in risk of losing its market share against the competition, moreover, it has been in the need of opening new market opportunities with the purpose of positioning and promote the program. This problematic place the next question for this investigation; How to establish accurate and detailed marketing strategies throughout social media for raking and active participation of the industrial engineering program in the digital local market? Concurrently, this investigation it’s developed by 4 stages; the first one introduce the analysis of the digital internal behavior of the University’s social media, this process is done by collecting and tabulating of the historical data obtained through the analytics software web (Rival IQ) based on the analysis of performance indicators (KPI). In second stage, interactions of direct competitors on social media are analyzed, in this case, direct competitors are University Santo Tomás, and University Corporation of Meta, using and repeating the same processes and tools as stage one. In the third stage, ranges of audience and market space are determined through the recollection of primary information using surveys, to meter the program of industrial engineering’s pertinence in the state/department of Meta, applied via online to students, graduated college students, teachers and business men involved in the regional industry. Ultimately, in last stage, strategies are defined to constitute the marketing plan in which the data base results are planned to create tactics and actions for marketing promotional material, which will be promoted with two videos, additionally the marketing plan will be promoted in the didactic factory of the university faculty.